Phototrophic sulfide oxidation: environmental insights and a method for kinetic analysis - Hanson, Thomas E.; Luther, George W.; Findlay, Alyssa; MacDonald, Daniel; Hess, Daniel (Frontiers in Microbiology, 2013)
Previously, we presented data that indicated microbial sulfide oxidation would out-compete strictly chemical, abiotic sulfide oxidation reactions under nearly all conditions relevant to extant ecosystems (Luther et al., 2011). In particular, we showed how anaerobic microbial sulfide oxidation rates were several orders of magnitude higher than even metal catalyzed aerobic sulfide oxidation processes. The fact that biotic anaerobic sulfide oxidation is kinetically superior to abiotic reactions implies that nearly all anaerobic and sulfidic environments should host microbial populations that oxidize sulfide at appreciable rates. This was likely an important biogeochemical process during long stretches of euxinia in the oceans suggested by the geologic record. In particular, phototrophic sulfide oxidation allows the utilization of carbon dioxide as the electron acceptor suggesting that this process should be particularly widespread rather than relying on the presence of other chemical oxidants. Using the Chesapeake Bay as an example, we argue that phototrophic sulfide oxidation may be more important in many environments than is currently appreciated. Finally, we present methodological considerations to assist other groups that wish to study this process.